Structural and Electrochemical Analysis of PMMA Based Gel Electrolyte Membranes - Chithra M. Mathew; K. Kesavan; S. Rajendran (International Journal of Electrochemistry)
New gel polymer electrolytes containing poly(vinylidene chloride-co-acrylonitrile) and poly(methyl methacrylate) are prepared by solution casting method. With the addition of 60 wt.% of EC to PVdC-AN/PMMA blend, ionic conductivity value 0.398×10-6 S cm−1 has been achieved. XRD and FT-IR studies have been conducted to investigate the structure and complexation in the polymer gel electrolytes. The FT-IR spectra show that the functional groups C=O and C≡N play major role in ion conduction. Thermal stability of the prepared membranes is found to be about 180°C.